HUBUNGAN TINGKAT PENDIDIKAN DAN USIA KEHAMILAN TERHADAP PERILAKU IBU HAMIL TENTANG CARA MENYIKAT GIGI DI KABUPATEN GIANYAR TAHUN 2021 - Ni Nengah Sumerti; Anak Agung Gede Agung; Anik Diantari; I G A Raiyanthi; I Nyoman Wirata (Jurnal Kesehatan Gigi (Dental Health Journal), 2022)
Pregnancy can affect dental and oral health including how to brush your teeth. This condition occurs an increase in levels of the hormones estrogen and progesterone, due to nausea and vomiting in the morning. The purpose of this study is to find out the relationship of knowledge level and gestational age to the behavior of pregnant women about how to brush their teeth in Gianyar Regency in 2021. This type of research is crossecsional research with survey methods using gooleform links. The respondents to this study were pregnant women at the time of KKN IPE which amounted to 45 people. The results showed respondents how to brush their teeth on the front how to going up and down as much as 57.78%, how to brush teeth on the side facing the cheeks by going up and down slightly twisting as much as 71.11%, how to brush teeth on the mastication by way back and forth as much as 100%, How to brush your teeth on the part facing the tongue and sky sky in a way gouging from the gums to the surface of the teeth as much as 60%. Bivariate analysis with a p value of of 0.05 showed no meaningful association between knowledge level and gestational age to pregnant women's behavior on how to brush their teeth. The conclusion of this study shows that most pregnant women brush their teeth in the right way and there is no relationship of knowledge level and gestational age to the behavior of pregnant women about how to brush their teeth.